Gambaran Entrepreneurial Self-Efficacy pada Mahasiswa UNPAD yang Menjalani Magang MSIB: Entrepreneurial Self-Efficacy Overview of UNPAD Students Undergoing MSIB Internship - Wijayanti, Puspita Adhi; Amalia , Rosaria Mita; Alam , Boy Yoseph Cahya Sunan Sakti Syah (ITScience (Information Technology and Science), 2024)
Entrepreneurial self-efficacy (ESE) is quite essential for starting a business. Many MSIB participants are interning at companies, which concerns the UNPAD Career Development Center regarding students' ESE. The study was conducted using a survey method: distributing a Google Forms questionnaire to the interns. The online process was used considering the location of the participants, who were spread out because they were undergoing an internship. The survey results showed that most students had relatively high ESE scores. The analysis of the difference test showed no significant difference in the scientific cluster and parental background, but the Science and Technology and Agrocomplex clusters had the highest average interest. Students with parents who work as entrepreneurs also have a higher level of confidence than students with parents who work as civil servants or private employees, BUMN and BUMD. Students' interest in entrepreneurship and ESE also show a significant relationship so that self-confidence will impact their interest in entrepreneurship, and they are expected to survive and develop. Parents' jobs and asking students to influence students' confidence in entrepreneurship. In addition, the Science and Technology and Agrocomplex clusters showed higher self-confidence in entrepreneurship. This study suggests providing entrepreneurial containers/opportunities for students to improve their entrepreneurial skills. In addition, a mentoring program is also needed to help students survive in their businesses and develop them into bigger businesses.